STUDI PENGEMBANGAN EKOTORISME DAN EVALUASI PENGELOLAAN KAWASAN HUTAN PADA AREAL PENGELOLAAN KPHL KOTA KUPANG - Nixon Rammang; Maria M. E. Purnama; Lusia Sulo Marimpan (Wana Lestari, 2019)
KPHL City of Kupang has a strategic role in creating forest sustainability, community welfare and at the same time accommodate the demands and interests of the central government and regional governments. Some of the strategies that can be done include optimizing community access to forests as an effort to resolve conflict, and improve community welfare. The exixtence of KPH organization at the field level thats close to the community will make it easier to understand the dynamic and the real issues at the field level, and at the same time being alternative solution for the conflict resolution. One of the potentials that is expected to be the main source of revenue for the Kupang City KPHL is Ecotourism. Ecotourism is a recreational and tourism activities that utilize the potential of natural resources, both in natural conditions and after cultivation. Ecotourism development is expected to begin in the first year of KPH Management. The initial step that is planned to be undertaken is to build supporting facilities and infrastructure such as gates, huts, food outlets, road infrastructure and conduct promotions. To be able to calculate the projected value of the economic benefits of nature tourism, it is necessary to develop business plans for each of these attractions. The strategies that can be carried out for ecotourism development in the KPH of Kupang City include the following; (1) promoting through social networking, (2) installing photographs and banners in places frequented by tourists, (3) selling tour packages based on tourist conditions and locations, (4) developing and fulfilling infrastructure (roads, facilities and other infrastructure (5) Participating in exhibitions organized by government and private institutions and (6) Promotion through the website.